Clinical Evaluation of Eugenia Jambolana Hypoglycemic Effects in Patients Diagnosed with Type II Non-Insulin Independent Diabetes - Zuhaib Ahmed, Mashkoor Ahmed Ansari, Iqra Ali, Fiza Soomro, Gunesh Kumar, Imran Joher, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Type 2 diabetes mellitus is a progressive hyperglycemic ailment in which blood glucose level increases than the normal values. Eugenia jambolana has anti-hyperglycemic properties. Objective: The study aimed to evaluate the hypoglycemic effects of Eugenia jambolana in patients, suffering from type II diabetes. Study design: A control-experimental study was performed at the Department of Pharmacology, Liaquat University of Medical and Health Sciences Jamshoro for the duration of six months from February 2022 to July 2022. Material and Methods: Patients with type 2 diabetes mellitus, having fasting glucose level greater than 140mg/dl and patients having uncontrolled diabetes, despite being on the anti-diabetic drugs, were included in the study as study subjects. The control group was comprised of individuals with blood glucose levels in normal ranges and had no previous family history of diabetes mellitus. The extracts of Eungenia jambolana were administered to the study subjects as per the approved plan and after which the blood glucose levels were determined. Results: Blood glucose levels were reduced in the group of patients, who were not on any antidiabetic medication. Urinary glucose levels were also investigated and glycosuria was found to be reduced. Reduction in blood glucose was also observed in the group, which was on oral hypoglycemics and the glucose levels were dramatically reduced with high dose. Conclusion: The extract of Eungenia jambolana exhibited lowering of blood glucose levels in diabetes patients and treated diabetes mellitus. It may be used alone or in combination with other hypoglycemic drugs for the effective blood glucose reduction and treatment of the disease. Keywords: Eungenia jambolana, type 2 Diabetes Mellitus.